Results based management for climate resilience and mitigation. Example from Latin America - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Researchers from CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) share approaches to Results Based Management. Featuring Dr. Bruce Campbell, Dr. Philip Thornton and Dr. Pramod Aggarwal. The session concludes with a Q&A with webinar participants. Webinar recorded on 10 January 2015.